Implementação de um inversor multinível monofásico com seis chaves semicondutoras controlado por dispositivo FPGA - Biava, Hiuri Franchinconi (2016)
In nowadays applications the efficient conversion of electrical energy has become greatly important. In this context, multilevel converters stand out amoung the main power electronics components for DC-AC conversion. This paper presents a study and implementation of a single-phase voltage inverter, using the multilevel topology cascaded with five levels and six semiconductor switches. The circuit is controlled by FPGA with the pulse width modulation technique implemented using VHDL language. Simulations were performed with different amplitude modulation factors to verify the control code’s behaviour and also the complete project. The driver circuit was validated. It is responsible for isolated transfer of the outputs programmed’s logic signal in the FPGA. This mechanism directly drives the gates of each IGBT that compose the inverter circuit. Moreover, the layout was developed to generate the PCB file used in board production. The results were obtained by resistive and resistive-inductive loading of circuit, simulating the motor’s application as a load. Results of analyzes considered different amplitude modulation factors, as well as harmonic spectrum study on resistive-inductive load. Finally, it was observed the proper operation of the circuit as expected according to the simulations.